Língua, cultura e cerveja: um estudo ecolinguístico de rótulos de cerveja artesanal - Pinheiro, Zilda Dourado (2018)
TThe general objective of this paper is describing and analysing the relations between language and culture in handmade beer labels produced in Brazil. This paper is grounded by Ecolinguistcs, a theory which studies language, people and territory in its mental, social and natural environments according to Couto (2016). The set of these interactions compose the linguistics ecosystem that, according to Couto (2018), is included at Cultural Ecosystem. The labels presents symbols that shows a imaginary of a determined brand of beer. Because of all these characteristics, the Brazilian handmade beer labels can produce a imaginary of each beer style that updates itself by language, the recipe and the label. It’s a Brazilian version of each beer style, how we can see at the names and the labels.